PENGARUH KARAKTERISTIK KADER TERHADAP KEAKTIFAN KADER POSYANDU DI DESA BAHUNG SIBATU-BATU KECAMATAN SEI DADAP KABUPATEN ASAHAN - Fitriani Pramita Gurning, SKM., M.Kes (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2016)
ABSTRACT Posyandu has an enormous role in increasing of health programs. The observations was found that the time of the implementation of posyandu activities target is not present routinely, so every month the achievement of the visit is still far from the target which has been determined monthly. This is related to community participation in supporting posyandu activities as well as participation of posyandu cadres themselves. Therefore it is necessary to conduct research on the influence of community participation on participation of cadres in Bahung village of Sibatu-batu Sei Dadap Sub-district of Asahan Regency. The type of research is descriptive analytic. The research was conducted in Bahung Sibatu-Batu Village, Sei Dadap Sub-district of Asahan Regency and conducted in July 2010. The population as well as the samples in this research are all active posyandu cadres in Bahung Sibatu-Batu Village, Sei Dadap Sub-district of Asahan Regency. The result of chi-square test shows that there is influence between education and knowledge of cadre to the activity of cadre in Bahung Sibatu-Batu Village, Sei Dadap Sub-district of Asahan Regency. The result of linear regression test shows that the most influential factor on the activeness of the cadres is knowledge and education. Suggested to: 1) District Health Office through Puskesmas to provide retraining of cadres so that the cadres can continue to participate by always be routinely present in posyandu activities; 2) Posyandu cadres to further improve their activities in posyandu activities and invite the community to be more active in posyandu activities. Keywords: Characteristics, Activity, Cadres, Posyandu